2020
DOI: 10.1136/flgastro-2020-101592
|View full text |Cite
|
Sign up to set email alerts
|

Reduced survival after upper gastrointestinal bleed endoscopy in the COVID-19 era is a secondary effect of the response to the global pandemic: a retrospective cohort study

Abstract: ObjectiveThe COVID-19 pandemic has placed increased strain on healthcare systems worldwide with enormous reorganisation undertaken to support ‘COVID-centric’ services. Non-COVID-19 admissions reduced secondary to public health measures to halt viral transmission. We aimed to understand the impact of the response to COVID-19 on the outcomes of upper gastrointestinal (UGI) bleeds.Design/methodsA retrospective observational multicentre study comparing outcomes following endoscopy for UGI bleeds from 24 March 2020… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
22
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(28 citation statements)
references
References 22 publications
5
22
1
Order By: Relevance
“…Five studies 21 , 24 27 with a total of 183 COVID-positive subjects reported the case fatality rate in confirmed COVID-19 patients undergoing GI endoscopy ( Figure 3(a) ). Random-effects meta-analysis demonstrates that the total case fatality rate is 0.17 (95% CI = 0.02–0.38).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Five studies 21 , 24 27 with a total of 183 COVID-positive subjects reported the case fatality rate in confirmed COVID-19 patients undergoing GI endoscopy ( Figure 3(a) ). Random-effects meta-analysis demonstrates that the total case fatality rate is 0.17 (95% CI = 0.02–0.38).…”
Section: Resultsmentioning
confidence: 99%
“…Four studies 13 , 24 27 with a total of 68 COVID-positive patients pointed out the complication rate in confirmed COVID-19 patients who have undergone GI endoscopy ( Figure 3(b) ). The pooled complication rate is 0.00 (95% CI = 0.00–0.02), and there is no statistically significant difference between the European group and the North American Group ( p -value = 0.90) using a fixed analysis.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…16 To stop the spread of the virus, many patients stayed at home. Secondary effects attributed to a reduction of service provision and the avoidance of healthcare have been sadly observed, including increased mortality from upper gastrointestinal bleeding in London 17 and a reduction in endoscopic gastrointestinal cancer diagnoses at a large UK centre. 18 Furthermore, nationwide lockdowns have led to both an increase in sedentary behaviour and alcohol consumption 19 with a subsequent increase in the number of patients with severe alcohol-related liver disease observed in a London teaching hospital…”
mentioning
confidence: 99%